A Study of Job autonomy and Job proficiencies of B School Faculties in Delhi/NCR Region (International Journal of Innovative Research in Engineering & Management, 2021)
The teacher shortage is an international problem, teacher job  satisfaction merits closer attention. Not only is job satisfaction  closely related to teacher retention, but it also contributes to the  well-being of teachers and their students, overall school cohesion,  and the enhanced status of the teaching profession. The goal of  this research was to look at the link between work autonomy and  job proficiency in instructors. The study also looked at the most  important aspects of work proficiency. Two surveys on 100 teachers took part in the research, with 42 men and 58 women  were used to collect data for this study in Delhi/NCR area private  B-schools. Work autonomy is highly associated with job  proficiency, according to the findings. It also revealed that  respondents had a high degree of work proficiency and autonomy.  Furthermore, money was reported to be the least satisfying feature  among instructors in this study. The teachers' experience, gender,  work proficiencies, and job autonomy had no significant  relationship. Finally, this research has instructive implications for  the management who want to create a happy working  environment for their teachers.
Keywords: Autonomy; Education; Proficiencies; School; Teachers